A Dermatological Safety Test of a Face Serum Formulation Derived from Honey and Propolis of Stingless Bee from East Kalimantan - Dewi, Januartha Kisari; Toruan, Vera Madonna Lumban; Paramita, Swandari; Arung, Enos Tangke (Future Science / FSH-PH Publications, 2024)
Skincare, which is a type of cosmetics, is an essential component in the process of maintaining and caring for the skin. It is known that the skin quickly absorbs the tiny molecular structure of serum. Stingless bees, widespread in East Kalimantan and Indonesia, benefit the skin's health by producing honey and propolis. This research aims to demonstrate that a face serum derived from honey and propolis of stingless bees from East Kalimantan is safe for use on the skin using dermatological standards. Here we will see whether there are allergic reactions and irritation from using facial serum. Using the Repeated Open Application Test (ROPT) technique, 20 volunteers were subjected to applying a face serum containing honey and stingless bee propolis. The serum was given to the upper arm twice daily for seven days. As part of the test, allergic reactions were evaluated using the system developed by the International Contact Dermatitis Research Group (ICDRG), and irritating reactions were evaluated using the Primary Irritation Index (PII). The results showed that on the first day, four of the volunteers reported moderate irritation reactions. Consequently, they scored 0.7, indicating they suffered minor irritation. On the other hand, the reactions of the remaining 16 volunteers were typical. Twenty participants had normal skin from the second treatment until the seventh day. The overall findings show that the facial serum based on honey and kelulut propolis from stingless bees from East Kalimantan showed a mild irritation reaction at the beginning of use and was safe to use in subsequent uses.